Molecular structure of amyloid and prion fibrils: insights from solid state NMR - Tycko, Robert (Henry Stewart Talks, 2008)
Overview of solid state NMR methodology, Structural model for Alzheimer's beta-amyloid fibrils, Self-propagating polymorphism in amyloid fibrils, Molecular basis of beta-amyloid polymorphism, Extension of solid state NMR methods to amylin fibrils and yeast prion fibrils, Structural basis of the generic nature of amyloid formation
Reviewed at 2020/05/01